2020
DOI: 10.21608/taec.2020.21902.1012
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Different Geographical Locations on Genetic Variation and Phytochemical Constituents of Two Medicinal Marine Algae.

Abstract: Genetic variations and phytochemical constituents of Dictyota dichotoma and Sargassum dentifolium, collected from Hurghada and Abu-Qir bay, were investigated. Results revealed an increase in the concentrations of carotenoids, sugars and DPPH% in the samples of both algal species collected from Hurghada as compared with those collected from Abu-Qir. Regarding the samples collected from Hurghada, an increase in the concentrations of chlorophyll a, b and phenols was recorded in S. dentifolium; while a decrease in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 58 publications
0
0
1
Order By: Relevance
“…ined., which thermal optimum is undoubtedly higher than that of other strains. Several studies have shown that the geographic locations or localities and also seasonal variations could affect the chemical composition and the production of bioactive compounds in algae [45,46]. However, in our study if the thermal optimum is respected, the EMn productivity seem not too much related to strain origin.…”
Section: Discussioncontrasting
confidence: 60%
“…ined., which thermal optimum is undoubtedly higher than that of other strains. Several studies have shown that the geographic locations or localities and also seasonal variations could affect the chemical composition and the production of bioactive compounds in algae [45,46]. However, in our study if the thermal optimum is respected, the EMn productivity seem not too much related to strain origin.…”
Section: Discussioncontrasting
confidence: 60%